Phenotypic PIA-Dependent Biofilm Production by Clinical Non-Typeable Staphylococcus aureus Is Not Associated with the Intensity of Inflammation in Mammary Gland: A Pilot Study Using Mouse Mastitis Model - Jully Gogoi-Tiwari (MDPI AG, 2021)
Non-typeable (NT) Staphylococcus aureus strains are associated with chronic bovine mastitis. This study investigates the impact of biofilm formation by clinical NT S. aureus on cytokine production and mammary tissue damage by using a mouse mastitis model. Mice infected with two different NT S. aureus strains with strong and weak biofilm forming potential demonstrated identical clinical symptoms (moderate), minimal inflammatory infiltrates, and tissue damage (level 1 histopathological changes) in the mammary glands. However, the S. aureus load in the mammary glands of mice and the level of pro-inflammatory cytokines (IL-1β, IL-6, IL-12, IL-17 and IFN-γ) in serum were significantly higher (p ≤ 0.05) in those infected with the strong biofilm forming NT S. aureus strain. The level of IL-6 in sera samples of these mice was extremely high (15,479.9 ± 532 Pg/mL). Furthermore, these mice died in 24h of post infection compared to 30 h in the weak biofilm forming NT S. aureus infected group. The study demonstrates no association between the strength of PIA (polysaccharide intercellular adhesion)-dependent biofilm production by clinical NT S. aureus and mammary gland pathology in a mouse mastitis model. However, the role of biofilm in the virulence of S. aureus advancing the time of mortality in mice warrants further investigation.